A case of bilateral hip and knee osteonecrosis in a patient with ankylosing spondylitis who used steroids due to immune thrombocytopenic purpura - Öztekin, Saadet Nur Sena; Sonmez, Rafet; Sarsan, Ayşe; Alkan, Hakan (Journal of Surgery and Medicine, 2021)
We aim to present a case of bilateral hip and knee osteonecrosis due to steroid use in an ankylosing spondylitis (AS) patient who developed immune thrombocytopenic purpura (ITP) after the use of nonsteroidal anti-inflammatory drugs (NSAID). A 60-year-old male patient was diagnosed with AS with bilateral sacroiliitis and inflammatory low back pain on sacroiliac radiography 10 years ago. He was followed up with NSAIDs. Intravenous steroid treatment was started in the hematology clinic to the patient who had developed ITP due to NSAID usage. The patient presented to our clinic with bilateral hip pain that developed after steroid therapy. He had limited hip joint movement and bilateral destructive hip joints in pelvic radiography. Bilateral total hip arthroplasty (THA) was performed by the Orthopedics and Traumatology Department at 1-year intervals because of osteonecrosis associated with steroid use. When he presented to our clinic 3 years later with bilateral knee pain, we detected osteonecrosis in the distal segments of bilateral femurs and proximal tibial diaphysis on knee MRI. We implemented a rehabilitation program with the conservative treatment recommendation of orthopedics. Comorbidities or drug side effects should be examined more carefully while treating peripheral joint involvement in patients with AS.